Rheological characterization and print quality studies of gelatin/collagen I/PEGDA hydrogels - Bartholomew, Kami; Mahapatro, Anil (International journal of polymeric materials, 2025)
Bioprinting is an up-and-coming technology that uses the basis of additive manufacturing and applies it to the field of tissue engineering. Bioprinting is used to create 3D models of diseased tissue and organs, test cellular responses to drug therapies, and create potentially transplantable organs and vasculature. Bioprinting has gained increasing interest especially in drug discovery, as the traditional 2D cell culture models have been shown to produce results that are not mimicked in animal and human trials. Bioprinters use materials called bioinks, developed from hydrogels which can contain cells and biological factors. While there are commonly used bioinks, there is a need for the development of a diverse range of bioinks for varying applications. In this study, an alternative bioink was developed. The formulations included gelatin, collagen I, and varying amounts of poly (ethylene glycol) diacrylate (PEGDA). These formulations were subject to rheological characterization and print quality analysis. Formulations with higher concentrations of PEGDA had higher degrees of shear-thinning, higher viscosity recovery, lower viscosities, and less dominant gel behavior. The print quality studies showed that the formulations with lower concentrations of PEGDA had better printability, print accuracy, and print fidelity. Formulation P5 had the best overall print quality.